Bilateral macular hole formation secondary to sclopetaria caused by shockwaves transmitted by a posterior vector: case report - Garcia Gerardo; Patel Chirag; Olson Jeff; Oliver Scott; Navarro Alicia; Kunjukunju Nancy; Mandava Naresh; Quiroz-Mercado Hugo (BMC Ophthalmology, 2010)
Abstract Background Sclopetaria is a rare ophthalmic finding in trauma Case Presentation This is a report of a patient who developed macular holes from sclopetaria induced by indirect trauma. A 22-year-old male, suffered a gunshot wound that passed behind his eyes, resulting in bilateral macular hole formation Conclusion To our knowledge, this is the first reported case in which trauma posterior to the globes caused bilateral macular hole formation